Politics and the Primary Teacher. - Cunningham, Peter (Understanding primary education series., 2011)
Why is primary education so high on the political agenda, and so contentious? Why is the performance of primary schools so often in the media spotlight? Why should primary teachers trouble themselves with the politics of their work? Politics and the Primary Teacher is an accessible introduction to some of the thorniest aspects of a primary teacher's role. It aims to support your understanding of the constant changes in education policy, give you confidence to engage critically with current political debates, and consider how you might shape your response accordingly. Including questions for re.